A Content Analysis of Financial Literacy in Children’s Storybooks in the Indonesian Book Information System (SIBI) Kemendikbud - Rizki Utami; Fitri Puji Rahmawati (Papanda Publisher, 2026)
Financial literacy is an important skill that needs to be introduced from an early age so that children are able to manage their finances wisely in the future. Children's storybooks are a potential medium for installing the concept of financial literacy in a contextual manner that is appropriate for children's cognitive development. Current research focuses heavily on financial literacy in print books, teaching materials, and other media. Research on financial literacy in online media remains limited. The purpose of this study is to describe financial literacy and identify forms of financial literacy in children's storybooks for early readers at levels B1, B2, and B3 at SIBI Kemendikbud. This study uses a qualitative approach with content analysis. The data sources were two children's storybooks, namely Tiup! Tiup! (level B2) and Ini atau Itu? (level B3). The research instruments were compiled based on financial literacy indicators, which included earning money, saving, spending, donating, managing finances, and distinguishing between needs and wants. The results of the study show that the book Tiup! Tiup! emphasizes the aspects of saving, spending in a planned manner, and simple financial management, but does not yet show the process of earning money and donating. Meanwhile, the book Ini atau Itu? contains more diverse financial literacy indicators, including earning money through business and the ability to distinguish between needs and wants. Neither book explicitly includes the aspect of giving. These results underscore the importance of developing children's storybooks that not only present engaging narratives but also integrate financial literacy in a balanced way appropriate to the child's stage of development.